(untitled) (Revista Paradigma, 2022)
Brazilian Family Law fosters shared custody as a path to coparenting, but there may be other means to ensure the effective sharing of childcare by divorced parents, minimizing conflicts, such as the way of paying for alimony. The aim of this study was to compare the incidence of conflict and parenting of divorced parents with underage children who pay for alimony set at a monetary value and those who do so “in natura”. Sixteen divorced male with at least one minor child participated in the survey. Participants were divided into two groups: Group 1, consisting of eight parents who fulfill the maintenance duty by means of alimony fixed at monetary value and Group 2, by eight parents who fulfill the maintenance duty by paying alimony “in natura”. The content of the interview transcripts was analyzed and categorized. The results showed differences between the two groups regarding feelings, conflicts and parenting. Group 1 revealed negative feelings, a higher incidence of conflicts with the former spouse and the exercise of parenting associated with relationship difficulties with the other parent. In group 2, the participants’ feelings were more positive, the rarer conflicts and the exercise of parenting described focusing on the paternal-filial relationship, without reference to other factors. The way of fulfilling the maintenance duty can be an alternative way to reduce contentious relationships and increase the exercise of parenting, which are essential factors for the satisfactory development of children and young people.